The Right to Obtain Free Assistance and Legal Protection for The Indigent People Through Legal Assistance Organizations - Mandjo, Julius; Sarson, Mohamad Taufik Zulfikar (Universitas Negeri Gorontalo, 2021)
The purpose of this study is to analyze the right to obtain free legal assistance and protection for indigent people through legal aid organizations in Gorontalo city. This research was conducted using an empirical juridical approach. The legal issues continue to occur in big cities and other provinces, such as Gorontalo province, as the 32nd province in Indonesia. Legal issues that are increasingly happening from both the upper and lower classes are still a problem in the jurisdiction of the Gorontalo district court. However, sometimes the problems that afflict the indigent people have minimal legal protection, even though they have constitutional rights as citizens to obtain legal assistance for the indigent people in the constitution. Act number 16 of 2011 concerning Legal Aid, even the Gorontalo government has issued Gorontalo Provincial Regulation Number 10 of 2015 concerning the implementation of Legal Aid for the indigent people. With the aim that all people have the right to obtain legal assistance for free or free of charge.